2020
DOI: 10.1007/s12298-020-00906-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and mapping of seed coat impermeability in soybean using inter-specific populations

Abstract: Seed coat impermeability (SCI) in soybean is associated with seed viability under storage and quality of processed products. Understanding genetics and identification of linked molecular markers would facilitate need-based utilization of seed coat impermeability. Two impermeable wild type (G. soja Sieb. and Zucc.) accessions viz. PI 424079 and PI 136620 were crossed with a permeable cultivated (G. max) variety JS335 to generate the mapping populations. Genetic analysis of the F 1:2 and F 2:3 seeds of the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Causes of such discrepancies include variation in tested genotypes, populations used, approached followed, criteria adopted, etc. (Chandra et al 2020) The studies reported earlier have had used seeds stored for one or two years only. Further, no reports could be found where wild type soybeans viz.…”
Section: Introductionmentioning
confidence: 99%
“…Causes of such discrepancies include variation in tested genotypes, populations used, approached followed, criteria adopted, etc. (Chandra et al 2020) The studies reported earlier have had used seeds stored for one or two years only. Further, no reports could be found where wild type soybeans viz.…”
Section: Introductionmentioning
confidence: 99%
“…A point mutation (G to T at the 863 rd site of its coding sequence) introduced an amino acid substitution (Ser to Iso at the 288 th site of its protein sequence) in a substrate-binding cleft of the enzyme, possibly reducing or eliminating its affinity for substrates in permeable cultivars from various regions, while the allele from the HS genotype was found to promote the accumulation of b-1,4-glucan derivatives that reinforce the HS trait (Jang et al, 2015). The above two genes are both located within the previously reported chromosome 2 interval and are adjacent in position (Sakamoto et al, 2004;Liu et al, 2007;Kebede et al, 2014;Chen et al, 2019;Chandra et al, 2020) and may be related to the strength of the palisade layer of the seed coat. Wang et al (2022) found that a polygalacturonase gene PG031 (Glyma.06G207300) was specifically expressed in the flowers and reproductive tissues of soybean plants, and that it was strongly induced when the seed coat absorbs water.…”
Section: Genes Related To Hs In Soybeanmentioning
confidence: 83%
“…Based on bulked segregant analysis and traditional linkage mapping, three HS QTLs were detected on chromosomes 2, 3, and 6, respectively, which explained 4.9%-23.3% of the phenotypic variation. Chandra et al (2020) constructed 204 RILs by crossing two wild soybean accessions with a permeable soybean cultivar, and seven HS QTLs were mapped on chromosomes 2, 5, 12, 13, and 16, respectively, explaining 5.96%-39.67% of the phenotypic variations. Two main and stable QTLs distributed in tandem on chromosome 2 were consistent over the 3 years of testing, and they jointly explained 43.09%-62.92% of the phenotypic variations of the HS trait.…”
Section: Qtl Mapping Of Hs Trait In Soybeanmentioning
confidence: 99%
“…A point mutation (G to T at the 863rd site of its coding sequence) introduced an amino acid substitution (Ser to Iso at the 288th site of its protein sequence) in a substrate-binding cleft of the enzyme, possibly reducing or eliminating its affinity for substrates in permeable cultivars from various regions, while the allele from the HS genotype was found to promote the accumulation of β-1,4-glucan derivatives that reinforce the HS trait [86]. The above two genes are both located within the previously reported chromosome 2 interval and are adjacent in position and may be related to the strength of the palisade layer of the seed coat [5,40,41,84,85]. Wang et al, [87] found that a polygalacturonase gene PG031 (Glyma.06G207300) was specifically expressed in the flowers and reproductive tissues of soybean plants, and that it was strongly induced when the seed coat absorbs water.…”
Section: Genes Related To Hs In Soybeanmentioning
confidence: 94%
“…Based on bulked segregant analysis and traditional linkage mapping, three HS QTLs were detected on chromosomes 2, 3, and 6, respectively, which explained 4.9%-23.3% of the phenotypic variation. Chandra et al, [85] constructed 204 RILs by crossing two wild soybean accessions with a permeable soybean cultivar, and seven HS QTLs were mapped on chromosomes 2, 5, 12, 13, and 16, respectively, explaining 5.96%-39.67% of the phenotypic variations. Two main and stable QTLs distributed in tandem on chromosome 2 were consistent over the 3 years of testing, and they jointly explained 43.09%-62.92% of the phenotypic variations of the HS trait.…”
Section: Qtl Mapping Of Hs Trait In Soybeanmentioning
confidence: 99%